2003
DOI: 10.1099/jmm.0.05224-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofilm formation by clinical isolates of Mycobacterium avium

Abstract: Mycobacterium avium is an environmental organism encountered in natural and urban water sources as well as soil. M. avium biofilm has recently been identified on sauna walls and in city water pipes and might have a role in the survival of virulent strains in the environment and in the host. To characterize the M. avium biofilm, an in vitro model was adapted wherein biofilm develops on a PVC surface. Biofilm was detected by staining with crystal violet and visualization by optical microscopy and quantified by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
154
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 21 publications
2
154
0
Order By: Relevance
“…Although the in vivo formation of biofilms by M. tuberculosis remains a matter of debate (21), it is well established that Mycobacterium smegmatis and other environmental mycobacteria such as M. avium subsp. avium, M. fortuitum, M. chelonae, and M. marinum are capable of biofilm formation (7,14,40). These mycobacteria are normal inhabitants of a wide variety of environmental reservoirs, including natural and municipal waters.…”
mentioning
confidence: 99%
“…Although the in vivo formation of biofilms by M. tuberculosis remains a matter of debate (21), it is well established that Mycobacterium smegmatis and other environmental mycobacteria such as M. avium subsp. avium, M. fortuitum, M. chelonae, and M. marinum are capable of biofilm formation (7,14,40). These mycobacteria are normal inhabitants of a wide variety of environmental reservoirs, including natural and municipal waters.…”
mentioning
confidence: 99%
“…Mycobacterium smegmatis, as well as M. avium, has been shown to produce a biofilm or a biofilm-like structure (6,19). The outermost layers of the M. smegmatis and M. avium cell walls contain glycopeptidolipid (GPL), whereas the outermost layer of M. tuberculosis is made of phenolic glycolipids, dimycocerosate, and lipo-oligosaccharides (24).…”
mentioning
confidence: 99%
“…Interestingly, such growth pattern of mycobacteria have frequently been noted in the literature as aggregation of cells driven by their surface hydrophobicity, and largely been ignored ever since Dubos and colleagues reported a method to grow dispersed culture of tubercle bacilli without diminishing their virulence (Dubos et al, 1946). However, the emerging concept of microbial persistence in biofilms have recently led several groups to investigate the detergent-free in vitro growth of mycobacterial species from the perspective of organized multicellular structures (Hall-Stoodley & Lappin-Scott, 1998, Carter et al, 2003. In one of the first genetic studies of surface associated growth of mycobacteria, Kolter and colleagues observed that an M. smemgatis mutant deficient in biosynthesis of acetylated glycopeptidolipid was also unable to attach and grow on an abiotic surface, thus demonstrating a specific genetic requirement for surface-associate mycobacterial growth (Recht & Kolter, 2001).…”
Section: Could M Tuberculosis Infections Persist As Biofilms?mentioning
confidence: 99%